Penyediaan Lembar Kerja Siswa Inovatif Larutan Elektrolit dan Non Elektrolit Untuk Siswa SMA - Ramlan Silaban; Sary MF Sitompul; Marianna E Pasaribu; Trisna W Simanullang (Pascasarjana Universitas Negeri Medan, 2015)
Abstract. This study aimed to obtain a student worksheet (LKS) on electrolyte and non electrolyte solution based innovative PBL and its influence on learning outcomes, affective and psychomotor attitudes of high school students. To achieve the objectives, conducted quasi-experimental research which starts from the assessment of some chemical LKS electrolyte and non-electrolyte solution that is used by high school students of class X, compile worksheets based innovative PBL, standardize, and limited test. There are two types of instruments in this research instrument a questionnaire BSNP non test and test instrument in the form of a multiple choice test is valid. The results obtained from this study: (1). Student worksheet (LKS) electrolyte and non electrolyte solution developed already meet the standards set by the National Education Standards. (2) The results of the student learning outcomes of senior high school students that learned using innovative worksheets on the electrolyte and non-electrolytes is higher than using an existing worksheet. (3). Affective percentage of students that learned using innovative worksheets on the electrolyte and nonelectrolytes is higher than using existing worksheets. (4). Psychomotor percentage of students that learned using innovative worksheets on the material and the electrolyte and nonelectrolytes is higher than using existing worksheets. Keywords: LKS inovatif, problem based learning, larutan elektrolit dan nonelektrolit